Analisis Bahasa Pelaku Ujaran Kebencian Berpotensi Hukum Terhadap Lesty Kejora Pada Laman Instagram @Lambe_Turah: Kajian Luinguistik Forensik - Riswanda Himawan; Zamzani Zamzani (Universitas Negeri Padang, 2022)
Speech in language is one part of the results of the interpretation of the human speech apparatus. Speech is closely related to the mindset of the person who pronounces it. The existence of social media, which is very developed today, is considered to make it easier for someone to convey thoughts or feelings to others. The development of social media today, raises perpetrators of language crimes as examples of hate speech. The hate test is carried out against one person against another. In line with that statement. This study aims to describe the language used by the perpetrators of hate speech to Lesty Kejora in the Instagram comments page, @Lambe_Turah. This research is included in the type of qualitative descriptive research. The source of the data used in this study is the comments of netizens contained in the comments page of the Instagram account @lambe_turah related to the news of the birth of Dangdut's first son Lesty Kejora. Data collection was carried out using the listen method by listening to comments written by netizens on the @lambe_turah Instagram comment page. The data collection technique in this study used tapping techniques and advanced techniques, including free-to-talk. The references used are the opinions of experts conveyed through research that is relevant to this research. The results showed that hate speech was found with 20 expressive utterances, 7 assertive utterances, 18 directives and 15 declarative utterances. Overall, Warganet made hate speech against Lesty Kejora, because of their lack of understanding in reading, they only participated between one netizen and another, reciprocating comments, resulting in hate speech that has the potential to be legal and have legal implications.